Analisis Dampak Inovasi Teknologi pada Strategi Manajemen Rumah Sakit - Lelyana, Nora (Jurnal Ilmu Sosial dan Humaniora, 2024)
Abstract: Technological innovation has revolutionized hospital strategic management, impacting operational efficiency, patient care quality, and leadership strategies. This research aims to analyze the multifaceted impact of technological innovation on hospital strategic management, focusing on three key dimensions: operational efficiency and resource allocation, patient care quality, safety, and satisfaction, and strategic implications for hospital leadership, governance, and long-term sustainability. Utilizing qualitative research methods, secondary data from recent literature and studies are analyzed to provide insights into the influence of technological innovation. Findings reveal that technological innovation enhances hospital workflows, optimizes resource allocation, improves clinical outcomes, enhances patient safety, and satisfaction, and necessitates strategic adjustments in leadership, governance, and investment strategies. The novelty of this research lies in its comprehensive analysis of the interplay between technological innovation and hospital strategic management, offering valuable insights for healthcare leaders, policymakers, and researchers. Keywords: hospital strategic management, leadership strategies, operational efficiency, patient care quality, technological innovation